Transforming education for a sustainable future: an analysis of teacher education in the context of climate change - Morales-Aguilar, Roberto; Arenas, Andoni; Cisternas, Delia; Bascopé, Martín; Salazar, Daniela; Becerra, Rukmini; Solís-Pinilla, Jaime; Merino, Cristian (Frontiers in Education, 2025)
In the specific context of geography and science teachers' training, socio-environmental problems, including climate change, highlight the need for professional development that facilitates the integration of social and environmental dimensions in favor of sustainability. This perspective seeks to promote wellbeing for all within planetary limits. This article addresses key questions: how has teacher education been structured to address climate change? What topics, methodologies and strategies have been used in this training? Where are documented research studies located on the disciplinary/transdisciplinary spectrum? This study will present the main results and knowledge derived from bibliographic research carried out in accordance with the Prisma 2020 protocol, aimed at identifying trends, challenges and good practices in education for sustainability. The results reveal multiple perspectives, contents, strategies and methodologies that enable us to determine the existence of a gradient ranging from disciplinary perspectives of climate sciences to interdisciplinary approaches that glean knowledge from several disciplines, such as ecology, economics and social sciences. In addition to a broader perspective of climate change, involving not only scientific knowledge, but also local and indigenous knowledge and associated ethical and moral perspectives, which bring these approaches closer to the transdisciplinary perspective.